TEORI HUKUM ALAM DAN KEPATUHAN NEGARA TERHADAP HUKUM INTERNASIONAL - Lutfi, Khoirur Rizal (Jurnal Yuridis, 2014)
This study aims to present a view of natural law theories regarding the position of international law that should be viewed by the entire international community as a law that must be obeyed. In addition this paper also present the measurement of the ethical and moral recognition of international law and an attempt to be accepted by the international community. in the end the natural law view that the values that are universally understood divided into three principal. First, the recognition of treaty. Secondly, should not depriving. Third, recognition of international custom considered as though not a written law. Other theories view, that the obligation to state compliance with international law can be based on several aspects, namely, soul, economic, political and other aspects that must be protected by the international community. Although the view of natural law often unwritten form, further action the values must be constructed in the form of awritten according to the needs of the international community